Novel Ferulic Amide Ac6c Derivatives: Design, Synthesis, and Their Antipest Activity - Zhang, Renfeng; Guo, Shengxin; Deng, Peng; Wang, Ya; Dai, Ali; Wu, Jian (Journal of agricultural and food chemistry, 2021)
Thirty-eight novel ferulic amide 1-aminocyclohexane carboxylic acid (Ac6c) derivatives D1–D19 and E1–E19 were designed and synthesized, and their antibacterial, antifungal, and insecticidal activities were tested. Most of the synthesized compounds displayed excellent activity againstXanthomonas oryzae pv. oryzae (Xoo), with EC50 values ranging from 11.6 to 83.1 μg/mL better than that of commercial bismerthiazol (BMT, EC50 = 84.3 μg/mL), as well as much better performance compared to that of thiediazole copper (TDC, EC50 = 137.8 μg/mL). D6 (EC50 = 17.3 μg/mL), D19 (EC50 = 29.4 μg/mL), E3 (EC50 = 29.7 μg/mL), E9 (EC50 = 27.0 μg/mL), E10 (EC50 = 18.6 μg/mL), and E18 (EC50 = 20.8 μg/mL) showed much higher activity on Xanthomonas oryzae pv. oryzicola compared with BMT (EC50 = 80.1 μg/mL) and TDC (EC50 = 124.7 μg/mL). In relation to controlling the fungus, Rhizoctonia solani, E1, E10, and E13 had much lower EC50 values of 0.005, 0.140, and 0.159 μg/mL compared to hymexazol at 74.8 μg/mL. Further in vivo experiments demonstrated that E6 and E12 controlled rice bacterial leaf blight disease better than BMT and TDC did. Scanning electron microscopy (SEM) studies revealed that E12 induced the Xoo cell membrane collapse. Moreover, D13 (73.7%), E5 (80.6%), and E10 (73.4%) also showed moderate activity against Plutella xylostella. These results indicated that the synthesized ferulic amide Ac6c derivatives showed promise as candidates for treating crop diseases.